2001
DOI: 10.1016/s0960-9822(01)00222-6
|View full text |Cite
|
Sign up to set email alerts
|

Hox genes and the phylogeny of the arthropods

Abstract: The arthropods are the most speciose, and among the most morphologically diverse, of the animal phyla. Their evolution has been the subject of intense research for well over a century, yet the relationships among the four extant arthropod subphyla - chelicerates, crustaceans, hexapods, and myriapods - are still not fully resolved. Morphological taxonomies have often placed hexapods and myriapods together (the Atelocerata) [1, 2], but recent molecular studies have generally supported a hexapod/crustacean clade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(119 citation statements)
references
References 18 publications
5
108
0
2
Order By: Relevance
“…However, studies from the field of molecular phylogeny (recent contributions, e.g., Shultz and Regier, 2000;Cook et al, 2001;Friedrich and Tautz, 2001;Hwang et al, 2001;Peterson and Eernisse, 2001;Regier and Shultz, 2001;Pisani et al, 2004) as well as morphological studies on the architecture of the nervous system recently have provided evidence for a close relationship of Hexapoda and Crustacea (reviews, e.g., Strausfeld, 1998Strausfeld, , 2005Schram and Koenemann, 2004;Harzsch et al, 2005a;Harzsch, 2006). The name "Tetraconata" has been suggested for a taxon that embraces the hexapods and crustaceans (Dohle, 2001;Richter, 2002) in reference to the tetrapartite crystalline cone in the ommatidia as a synapomorphy of these groups.…”
Section: Comparison To Eye Growth In Drosophila Melanogaster and Evolmentioning
confidence: 99%
“…However, studies from the field of molecular phylogeny (recent contributions, e.g., Shultz and Regier, 2000;Cook et al, 2001;Friedrich and Tautz, 2001;Hwang et al, 2001;Peterson and Eernisse, 2001;Regier and Shultz, 2001;Pisani et al, 2004) as well as morphological studies on the architecture of the nervous system recently have provided evidence for a close relationship of Hexapoda and Crustacea (reviews, e.g., Strausfeld, 1998Strausfeld, , 2005Schram and Koenemann, 2004;Harzsch et al, 2005a;Harzsch, 2006). The name "Tetraconata" has been suggested for a taxon that embraces the hexapods and crustaceans (Dohle, 2001;Richter, 2002) in reference to the tetrapartite crystalline cone in the ommatidia as a synapomorphy of these groups.…”
Section: Comparison To Eye Growth In Drosophila Melanogaster and Evolmentioning
confidence: 99%
“…Many studies have used phylogenetic tools to generate evolutionary topologies of Hox genes and other regulatory loci (e.g., Kim et al, 2003;Purugganan, 1997;Santini and Bernardi, 2005;Wagner et al, 2005) yet there are few explorations of the phylogenetic utility of regulatory gene sequences in in larger, multi-locus phylogenetic analyses. Several recent examples in arthropods (Cook et al, 2001) and plants (Barrier et al, 2001;Fan et al, 2004) have shown that regulatory loci can make strong contributions to phylogenetic resolution. This work, particularly in plants, has shown that regulatory gene sequences and their protein products do not necessarily evolve more slowly than structural genes, and in fact may evolve significantly faster (Barrier et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they support those molecular (e.g. Shultz and Regier 2000, Cook et al 2001, Giribet et al 2001, Hwang et al 2001, Peterson and Eernisse 2001, Regier and Shultz 2001a, b, Burmester 2002, Kusche et al 2002 and morphological studies (e. g. Dohle 1997, Paulus 2000, Harzsch 2001a, Nielsen 2001, Richter 2002, Schram and Koenemann 2004) that argue in favour of the Tetraconata concept and suggest a paraphyly of the Tracheata and Crustacea as we traditionally perceive these taxa.…”
Section: Phylogenetic Analyses Of Neurocharactersmentioning
confidence: 61%